Invitation Programme for Young Intellectuals in Southeast Asia 2015 - Wong, Bemen (Japan Foundation Kuala Lumpur, 2016)
Thanks to the Japan Foundation, I was selected to represent my university, Universiti Malaysia Sarawak, at a regional programme exploring the revitalisation of rural areas and creation of new values. I was among 11 young intellectuals from six countries; namely Thailand, Vietnam, Philippines, Indonesia, Singapore and Malaysia.